1985
DOI: 10.1093/nar/13.13.4739
|View full text |Cite
|
Sign up to set email alerts
|

A novel class of human type I interferons

Abstract: The screening of a cDNA library prepared from mRNA of Sendai virus induced Namalwa (human Burkitt's lymphoma) cells, using a human IFN-alpha 2 DNA probe under conditions of low stringency, identified two weakly hybridizing clones containing sequences related to, but discernably different from those of the IFN-alpha class. Sequence and hybridization analysis of these cDNAs as well as expression in E. coli provided evidence that they encode proteins which have the characteristics of IFN type I but which are suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
3

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(44 citation statements)
references
References 31 publications
0
41
0
3
Order By: Relevance
“…24 Owing to a sequence homology of about 60-70% between IFN-o and IFN-a, IFN-o was originally considered a subfamily of IFN-a (thus its old designation as IFN-a II). 25 Later, IFN-o was found in the sera of SLE, and it may also be a major IFN species produced by peripheral blood cells in SLE patients. 19,20,[26][27][28] In naturally occurring SLE, both circulating IFN-a and increased levels of IFN-a-inducible proteins, such as OAS1, OAS2, and OASL, have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…24 Owing to a sequence homology of about 60-70% between IFN-o and IFN-a, IFN-o was originally considered a subfamily of IFN-a (thus its old designation as IFN-a II). 25 Later, IFN-o was found in the sera of SLE, and it may also be a major IFN species produced by peripheral blood cells in SLE patients. 19,20,[26][27][28] In naturally occurring SLE, both circulating IFN-a and increased levels of IFN-a-inducible proteins, such as OAS1, OAS2, and OASL, have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The virus concentration was chosen so that about 95~ cytopathic effect was obtained after 24 h. At that time, the medium was removed, the cells were washed once with tap water, stained with 0.3 ~ methyl violet, washed and air dried. The absorbance Hauptmann & Swetly (1985). of the stained cell layers was determined using an ELISA reader equipped with a 540 nm filter.…”
Section: Interferonsmentioning
confidence: 99%
“…Recently, a third class I IFN gene family was discovered independently by Capon et al (1985), Feinstein et al (1985), and Hauptmann & Swetly (1985). In humans, this novel family consists of a single functional gene and at least three, probably four pseudogenes R.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the pig is an interesting model for investigating the role of endogenous IFN in viral infections and for studying the pharmacology and toxicology of exogenous homologous IFN (La Bonnardi6re et al, 1984). Recently we showed that, as in the human, bovine and equine species (Capon et al, 1985;Hauptmann & Swetly, 1985;Velan et al, 1985;Himmler et al, 1986), the porcine IFN-~ (PoIFN-~) multigene family can be divided into two homologous, but distinct classes of genes. The class I subfamily, located on porcine chromosome 1 (Yerle et al, 1986) contains at least 11 loci, of which nine have been cloned and two sequenced: PoIFN-~I and PoIFN-~2 (Lef6vre & La Bonnardi6re, 1986;F.…”
Section: Introductionmentioning
confidence: 99%